2020
DOI: 10.1021/acsnano.9b06731
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Imaging-Trackable Magnetic Microswimmers for Pathogenic Bacterial Infection Treatment

Abstract: Micro/nanorobots have been extensively explored as a tetherless small-scale robotic biodevice to perform minimally invasive interventions in hard-to-reach regions. Despite the emergence of versatile micro/nanorobots in recent years, matched in vivo development remains challenging, limited by unsatisfactory integration of core functions. Herein, we report a polydopamine (PDA)-coated magnetic microswimmer consisting of a magnetized Spirulina (MSP) matrix and PDA surface. Apart from the properties of the existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
188
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(189 citation statements)
references
References 86 publications
1
188
0
Order By: Relevance
“…[244] Later studies reported photothermal therapy against a mouse subcutaneous drug-resistant Klebsiella pneumonia infection model. [245] Despite considerable progress in reducing hunger in the world, more than one-third of the worldwide population still suf- Reproduced with permission. [232] Copyright 2019, Wiley.…”
Section: Inorganic Agentsmentioning
confidence: 99%
“…[244] Later studies reported photothermal therapy against a mouse subcutaneous drug-resistant Klebsiella pneumonia infection model. [245] Despite considerable progress in reducing hunger in the world, more than one-third of the worldwide population still suf- Reproduced with permission. [232] Copyright 2019, Wiley.…”
Section: Inorganic Agentsmentioning
confidence: 99%
“…1cm deep). [63][64][65] Another hurdle that needs to be considered is the complex environment inside the reproductive system in vivo, from which there is very little known from the literature,for example the oviduct hydrodynamics in the presence of oocytesa nd micromotors or the exact fertilization timing. Fortunately,v ersatile micromotors not only enable various bio-applications but can also be used as non-invasive microtools to study cell/tissue biophysics [66] or perform local sensing.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately,v ersatile micromotors not only enable various bio-applications but can also be used as non-invasive microtools to study cell/tissue biophysics [66] or perform local sensing. [63]…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Xie et al demonstrated magnetic actuation with photoacoustic tracking of magnetized Spirulina and off/on fluorescent detection of a bacterial infection in mice. [ 155 ] Photoacoustic computed tomography (PACT) has been used for the in vivo monitoring of a microrobotic system by Wu et al [ 154 ] The authors designed a gastrointestinal tract‐targeted system consisting of gold–magnesium micromotors, which were encapsulated into a hydrogel to protect them from the harsh conditions of the stomach. Upon oral administration, their distribution through the bowels was monitored by PACT.…”
Section: Active Motion For Improved Diffusion and Navigation Into Thementioning
confidence: 99%